Kahoot Application As A Formative Evaluation Media In Students’ Comprehension Of The Aspect Of Writing Narrative Text In Online Class (Qualitative Case Study At One Of Senior High School) - Mawardi, Luthfia Nurul Mawaddah; Rustandi, Andi (Journal of English Education Program (JEEP), 2024)
This article figures out the ways of applying Kahoot as a formative evaluation media in students' comprehension of the aspect of writing narrative text in an online class; and investigates the perceptions of the teacher of using Kahoot as a formative evaluation media in students' comprehension of the aspect of writing narrative text in an online class. The study applied a qualitative research design, employing the case study characteristics. The data were attained from some sources, including classroom observation and interviews. Classroom observation was conducted to 11 MIPA and the interview was administered to an English teacher. The findings revealed that implementing Kahoot in the process of evaluation can increase the student's achievement; so that student's comprehension of the narrative text can be improved. The teacher perceives that Kahoot helped carrying out the formative evaluation process in the online classroom because the teacher can easily see the level of students' understanding of aspects of writing narrative text. However, the evaluation process is hampered by unstable internet connections. The finding of this research recommended English teachers to apply technology, in particular, Kahoot, that can make the learning and evaluation process in online classes easier and more fun. Also, Kahoot helps students practicing and increasing their understanding towards the delivered materials.